Assessment of Risks Associated With Severe Acute Respiratory Syndrome Coronavirus 2 Experimental Human Infection Studies. (29th November 2020) - Kuiper, Vincent P; Rosendaal, Frits R; Kamerling, Ingrid M C; Visser, Leonardus G; Roestenberg, Meta
Abstract: Controlled human infection (CHI) models for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been proposed as a tool to accelerate the development of vaccines and drugs. Such models carry inherent risks. Participants may develop severe disease or complications after deliberate infection. Prolonged isolation may negatively impact their well-being. Through secondary infection of study personnel or participant household contacts, the experimental virus strain may cause a community outbreak. We identified risks associated with such a SARS-CoV-2 CHI model and assessed their likelihood and impact and propose strategies that mitigate these risks. In this report, we show that risks can be minimized with proper risk mitigation strategies; the residual risk, however, should be weighed carefully against the scientific and social values of such a CHI model. Abstract : Controlled human infection models of severe acute respiratory syndrome coronavirus 2 have inherent risks to the individual study participant and to third-party contacts. Risks may be minimized with proper risk mitigation strategies.